Artificial Intelligence (AI) and Digital Imaginary Contents in the 2024 Presidential Election Campaign in Indonesia - Waty, Reni Rentika; Zalpa, Yulion; Ihsan, A. Bakir; Fadli, Najmi Muhammad (Politika: Jurnal Ilmu Politik, 2025)
This research is an investigation into the utilization of artificial intelligence (AI) and digital content in the context of the 2024 presidential election campaign in Indonesia. This research employs a descriptive qualitative methodology to examine the ways in which three presidential and vice-presidential candidate pairs leverage AI technology and imaginary digital content in their campaign strategies. This research addresses the utilization of artificial intelligence (AI) technology and imaginary digital content as campaign strategies employed by three pairs ofcandidates in the 2024 presidential election. This research offers novel insights into the nexus between technology, digital media, and political processes. The analytical framework employed in this study is based on the political communication theories of Robert E. Denton, Judith S. Trent, and Robert V. Friedenberg. It focuses on the use of AI, message construction, image formation, use of media and communication channels, and audience segmentation and targeting. The findings revealed that the three candidate pairs employed disparate strategies regarding the utilization of AI and the visualization of imaginary digital content. The Prabowo-Gibran pair employed artificial intelligence extensively to cultivate a friendly and contemporary image. Ganjar-Mahfud employed artificial intelligence for the purposes of sentiment analysis and voter interaction. In contrast, the Anies-Muhaimin campaign employs chatbots with the objective of disseminating information regarding their policy positions.